Pengaruh Aplikasi Bioarang dan Zeolit pada Fluks CO2, Populasi Mikrob, dan Aktivitas Enzim Mikrob pada Gambut - Safira Eka Aprianti; Rahayu Widyastuti; Heru Bagus Pulunggono; Laksmita Prima Santi (Institut Pertanian Bogor, 2023)
Oil palm plantation on peatlands is considered to contribute to increasing global warming by releasing CO2 as one of the greenhouse gases that cause global warming. The addition of ameliorants, such as biochar and zeolite, can absorb CO2 from soil respiration and store and filter it in their molecular pores. This research aimed to study the effect of ameliorant application on the CO2 flux, water content, microbial population, and enzyme activities. Ameliorant was applied to peat soil with two factors. The first factor was an ameliorant combination with 6 treatment levels: control (A0); zeolite (A1); biochar (A2); zeolite:biochar 75:25; zeolite:biochar 25:75; zeolite:biochar 50:50, and the second factor was 3 levels dose of treatment (% w/w): 1.5%, 3%, and 4.5%. Peat flux CO2 and water content were measured monthly for four months in the laboratory. Without mixing with biochar (A1), the results showed that zeolite suppressed CO2 flux and suppressed the decrease of water content better than other ameliorant combinations. However, different ameliorant dosage percentages did not show any significant results. Ameliorant application and incubation affected the microbial population and enzyme activities, and the results were varied. Chemical characteristics changed after 4 months of incubation. In conclusion, our results indicate that only zeolite amendment can suppress CO2 flux and decrease water content but did not affect microbial population dynamics and enzyme activities. Keywords: ameliorant, CO2 flux, enzyme activities, lignocellulolytic microbes, peat